Respuesta agronómica de plantas de tomate (solanum lycopersicum l) a la aplicación de ácidos húmicos. - Briones García, Jefferson Fernando (2022)
The agronomic response of tomato plants (Solanum Lycopersicum L.) to the application of humic acids was carried out in Quevedo city, Los Rios province. The experimental design was completely randomized with three treatments and one control with four repetitions. The treatments were distributed as follows: T1: Control (No application), T2: Humic acids 1/10 v/v, T3: Humic acids 1/30 v/v, and T4: Humic acids 1/50 v/v. Variables were: plant height, number of flowers per bunch, number of bunches with flowers, number of fruits per bunch, number of bunches with fruits, number of fruits per plant, fruit polar diameter, fruit equatorial diameter, and fruit fresh biomass (kg). The results obtained were T4: 1/50 v/v, plant height 73.25 cm, 9 flowers per cluster, 20.75 bunches with flowers per plant, 7.75 fruits per cluster, 15.75 bunches with fruits, 89.50 fruits per plant, 8.70 cm fruit polar diameter, 6.65 cm fruit equatorial diameter and 201.27 kg of fruits.